Sceptical essays on human rights - Campbell, Tom; Ewing, Kieth; Tomkins, Adam (Oxford : Oxford University Press, 2001)
Table of Treaties and Legislation
1. Introduction: On Being Sceptical about Human Rights
Part One: Scepticism and Human Rights
2. Constitutive Citizenship versus Constitutional Rights: Republican
Reflections on the EU Charter and the Human Rights Act Richard Bellamy
3. Rights, Democracy, and Law
4. Legislative Sovereignty and the Rule of Law
5. Incorporation through Interpretation
6. The Unbalanced Constitution
7. Human Rights in a Postnational Order: Reconciling Political and
Constitutional Pluralism Neil Walker
Part Two: The Impact and Implications of the Human Rights Act
8. Rights versus Devolution
9. Contested Constitutionalism: Human Rights and Deliberative Democracy in
Northern Ireland Colin Harvey
10. Taking Wales Seriously
11. Scepticism under Scrutiny: Labour Law and Human Rights
12. Discrimination Law and the Human Rights Act 1998
13. Tort Law and the Human Rights Act
14. Criminal justice, judicial Interpretation, Legal Right: On Being
Sceptical about the Human Rights Act 1998 Alan Norrie
15. Minority Protection and Human Rights
Part Three: The Experience of Elsewhere: Reasons to be Sceptical
16. The South African Experience of Judicial Rights Discourse: A Critical
17. Rights-Based Constitutional Review in Central and Eastern Europe
18. The Canadian Charter of Rights: Recognition, Redistribution, and the
Imperialism of the Courts
19. Scepticism about judicial Review: A Perspective from the United States
20. The Effect of a Statutory Bill of Rights where Parliament is
Sovereign: The Lesson from New Zealand
21. The Australian Free Speech Experiment and Scepticism about the UK
Contents
List of Contributors
Table of Cases
Adam Tomkins
Martin Loughlin
Jeffrey Goldsworthy
Keywords: Civil rights -- Great Britain; Human rights; Human Rights; International law; Human rights; Politics; Democracy; Labour law; Courts; Rule of law; Europe; Northern Ireland; South Africa; Eastern Europe; Australia; New Zealand; United Kingdom; Droits de l'homme (Droit international); Civil rights; Human rights; Great Britain; International law; Human rights; Politics; Democracy; Labour law; Courts; Protection; EU Charter of Fundamental Rights; Rule of law